Why fathers cry at night ebook A memoir in love poems, letters, recipes, and remembrances. - Alexander, Kwame (2023)
This powerful memoir from a #1 New York Times bestselling author and Newbery Medalist features poetry, letters, recipes, and other personal artifacts that provide an intimate look into his life and the loved ones he shares it with. In an intimate and non-traditional (or "new-fashioned") memoir, Kwame Alexander shares snapshots of a man learning how to love. He takes us through stories of his parents: from being awkward newlyweds in the sticky Chicago summer of 1967, to the sometimes-confusing ways they showed their love to each other, and for him. He explores his own relationships—his difficulties as a newly wedded, 22-year-old father, and the precariousness of his early marriage working in a jazz club with his second wife. Alexander attempts to deal with the unravelling of his marriage and the grief of his mother's recent passing while sharing the solace he found in learning how to perfect her famous fried chicken dish. With an open heart, Alexander weaves together memories of his past to try and understand his greatest love: his daughters. Full of heartfelt reminisces, family recipes, love poems, and personal letters,  Why Fathers Cry at Night  inspires bravery and vulnerability in every reader who has experienced the reckless passion, heartbreak, failure, and joy that define the whirlwind woes and wonders of love.